Hydroconversion and deoxidation bifunctional catalyst for organic sulfur in feed gas and preparation method of hydroconversion and deoxidation bifunctional catalyst

By introducing rich pore structures and strengthening anchoring effects into the catalyst, the problems of low conversion efficiency of macromolecular organic sulfur and reduced catalyst activity are solved, and efficient hydrogenation and deoxygenation performance is achieved, which is suitable for industrial-scale promotion.

CN119425735APending Publication Date: 2025-02-14SOUTHWEST CHEM (MEISHAN) CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411330903.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing catalysts have low conversion efficiency when treating macromolecular organic sulfur such as thiophene, and their activity decreases after long-term operation, which easily leads to pore blockage due to carbon accumulation, affecting catalytic performance. At the same time, traditional catalysts react violently during the reaction, resulting in reduced activity and difficult to promote on industrial scale.

Method used

A bifunctional catalyst is used, including 65-85% support, 5-15% active component 1, 5-15% active component 2, 1-5% active additive, and 1-5% detachment. The mold agent and 1-5% pore-forming agent are prepared by co-precipitation method and mechanical mixing method to form a rich pore structure and strengthen the anchoring effect, thereby improving catalytic activity and resistance to carbon deposits.

Benefits of technology

It significantly improves the hydrogenation conversion of macromolecular organic sulfur such as thiophene, and the conversion of carbonylsulfide and ethylsulfide is increased by 30%, 20%, and 15%, respectively, which enhances the deoxygenation performance of the catalyst, reduces the export oxygen concentration, and avoids It has safety hazards caused by excessive oxygen and maintains high activity after long-term operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425735A_ABST
    Figure CN119425735A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a bifunctional catalyst for hydro-conversion and deoxidation of organic sulfur in feed gas and a preparation method of the bifunctional catalyst. The catalyst comprises a carrier, an active component I, an active component II, an active aid, a release agent and a pore forming agent. The carrier is modified in a coprecipitation mode, and the negative effects of high-temperature sintering, structural damage and the like are inhibited. The acid and the active auxiliary agent which can interact with the active component are added, so that activity reduction caused by relatively strong acting force between the active component and the carrier and embedding of the active component into a carrier crystal lattice is avoided, and the hydrodesulfurization and deoxidation performance of the catalyst is improved. The pore-forming agent is introduced in the preparation process, so that a rich pore structure can be constructed, the reaction active sites and the diffusion rate of macromolecular organic sulfur on the surface of the catalyst are increased, and the technical problems of pore blockage, catalyst deactivation and the like caused by carbon deposit are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas and a preparation method thereof. Background Art

[0002] Organic sulfides (thiophene, tetrahydrothiophene, carbon disulfide, carbonyl sulfide, mercaptans, sulfides, etc.) are a type of industrial catalyst poison that is difficult to decompose and remove. The presence of organic sulfides can cause poisoning and inactivation of various metal catalysts during the reaction, affecting the service life and activity of the catalyst. Therefore, the catalytic hydrogenation of organic sulfides into easily removable hydrogen sulfide has become a focus of attention in the field of catalysis. For example: coke oven gas is a combustible gas produced during the coking process. Its main components are methane, hydrogen, CO, CO2, olefins, nitrogen and oxygen. The sulfides contained in it are mainly derived from the sulfur contained in the bituminous coal itself, which is converted into organic sulfur and inorganic sulfur during the high-temperature distillation process. After the above-mentioned sulfur-containing impurities are purified by alkaline solution and separated by pressure swing adsorption with the coke oven gas, the sulfur content can still reach 20mg / Nm 3 , causing catalyst poisoning in the subsequent synthesis process. Catalytic hydrogenation of organic sulfur mainly converts various forms of organic sulfur into hydrogen sulfide, which is then removed by wet or dry desulfurization.

[0003] At present, the efficiency of hydrogenation conversion of macromolecular organic sulfur and the degree of catalyst activity decline after long-term operation have been recognized as key indicators for evaluating catalyst performance. The organic sulfur hydrogenation conversion catalysts disclosed in Chinese patents CN 115888752 A, CN 107486223A, CN114768875A, and CN 118179557A all have a certain comprehensive removal capacity for organic sulfur, but none of the above patents involve reports on hydrogenation conversion of macromolecular organic sulfur thiophenes. Other patents involving hydrogenation conversion of macromolecular organic sulfur thiophenes, such as CN 112354556A, CN 105435806 A, CN 103203236 B, and CN103157481 B, have not been tested for long-term operation, and the effect of carbon deposition caused by long-term operation on hydrogenation conversion performance has not been investigated.

[0004] In addition to stable operation and carbon deposition, existing patents fail to comprehensively consider industrial production and application scenarios. Patent CN 117483006 A discloses a catalyst for removing organic sulfur from coke oven gas and a preparation method. The catalyst has a complex process and some of its adsorption performance relies on physical adsorption. Chinese patent CN 112742362 A discloses a catalyst for hydrogenation desulfurization of coke oven gas and its preparation method and application. However, due to the small size of the catalyst, it is easy to cause excessive pressure drop in a short period of time, resulting in blockage of the reaction tube. The above patents are not conducive to large-scale industrial production.

[0005] In addition, since coke oven gas contains a small amount of oxygen, and coking production itself has a certain instability, the oxygen content in coke oven gas may increase in a short period of time, forming an explosive mixed gas, causing hidden safety accidents such as electric capture explosion. It is worth noting that patent CN 108855116 A discloses a low-load coke oven gas hydrodesulfurization catalyst and its preparation method and application, which can have the performance of deoxygenation, olefin saturation and hydrodesulfurization, but the wet kneading preparation method of introducing multiple active components in one step is more likely to cause reactions between active components, weakening the interaction with the carrier, resulting in the loss of active components during use and the decrease of catalytic activity.

[0006] Considering the complex components of the raw gas, the traditional organic sulfur hydrogenation conversion has violent side reactions during the reaction process, which leads to catalyst sintering, surface carbon deposition, and reduced reaction sites, which in turn causes a decrease in catalytic activity; at the same time, pore blockage will increase the diffusion resistance of certain sulfur-containing macromolecules on the catalyst surface, making it difficult to hydrogenate and convert them, and the catalyst deactivates quickly. Therefore, it is urgent to develop a bifunctional catalyst that has a high catalytic hydrogenation conversion effect on multiple organic sulfur components, has high deoxidation performance, and has a developed pore structure, strong resistance to carbon deposition, good heat dissipation effect, high strength, and can still maintain high activity after long-term operation. Summary of the invention

[0007] The purpose of the present invention is to provide a bifunctional catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas and a preparation method thereof in view of the defects of the current organic sulfur removal catalyst. The bifunctional catalyst prepared by the method has the advantages of high hydrogenation conversion efficiency, strong deoxygenation ability, rich pore structure, strong carbon deposition resistance, simple preparation and easy promotion, etc., which can better solve the problems existing in the existing catalysts in the background technology.

[0008] In order to achieve the purpose of the present invention, the specific technical scheme of the present invention is as follows:

[0009] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas. The catalyst comprises, by weight percentage, 65-85% of a carrier, 5-15% of an active component one, 5-15% of an active component two, 1-5% of an active auxiliary agent, 1-5% of a release agent and 1-5% of a pore-forming agent, and the total weight percentage is 100%.

[0010] As a better implementation in the present application, the carrier is a composite oxide material.

[0011] As a better implementation in the present application, the active component one is any one of Fe2O3, CuO, ZnO, CoO or a mixture of several thereof.

[0012] As a better implementation in the present application, the active component 2 is any one of NiO, MoO3, Cr2O3, WO3 or a mixture of several thereof.

[0013] As a better embodiment of the present application, the active auxiliary agent is any one of boric acid and boron nitride or a mixture of the two.

[0014] As a better implementation in the present application, the release agent is any one of graphite, magnesium stearate, and calcium stearate, or a mixture of several of them.

[0015] As a better implementation in the present application, the pore-forming agent is any one of polyacrylamide, polymethyl methacrylate, and linear phenolic resin, or a mixture of several of them.

[0016] As a preferred embodiment of the present application, the method for preparing a catalyst for hydrogenation conversion of organic sulfur in raw gas comprises the following steps:

[0017] (1) Weigh a certain amount of any one or a mixture of several of Zr, Ce, and La salts, add it to an appropriate amount of deionized water, place it in a 40-60° C. water bath and stir to dissolve, then weigh a certain amount of pseudo-boehmite powder and add it to the solution, and stir it at 400 rpm for 2-4 hours to obtain a solid-liquid mixed slurry A;

[0018] (2) Weigh a certain amount of sodium carbonate, potassium carbonate or ammonia water, any one or a mixture of several thereof, add an appropriate amount of deionized water, stir to dissolve, and then use a pump to pump into the solid-liquid mixed slurry A until the pH value of the solution is 9.8-10.0, then stir at 400 rpm for 4-12 hours, filter and wash three times after stirring, then dry at 120° C. for 6-12 hours, and then calcine at 600-800° C. in air for 5-10 hours to obtain a precursor B;

[0019] (3) Weigh a certain amount of the soluble salt of the active ingredient 1, add an appropriate amount of deionized water, place in a 40-60° C. water bath, stir and dissolve to obtain a precursor solution C;

[0020] (4) mechanically mixing the precursor B and the precursor solution C in a closed mud mill for 2-4 hours to obtain a precursor D; the absolute pressure in the closed mud mill is 0.001-0.05 MPa;

[0021] (5) drying the precursor D in the shade at 30-50° C. for 10-20 h, then heating to 120-150° C. for drying for 6-12 h, and then calcining in air at 400-550° C. for 4-6 h to obtain a precursor E;

[0022] (6) Weigh a certain amount of the soluble salt of the active component 2, add an appropriate amount of deionized water, place in a 40-60° C. water bath, stir and dissolve to obtain a precursor solution F;

[0023] (7) Weigh a certain amount of the active auxiliary agent, the release agent and the pore-forming agent, place them together with the precursor E in a closed mud kneading machine, then add the precursor solution F and an acid with an equal amount of substance to the precursor solution F, mix and knead for 2-4 hours, and then use a mechanical extruder or an extrusion ball making machine to extrude and shape, to obtain precursor G.

[0024] Preferably, the absolute pressure in the closed mud kneading machine is 0.001-0.05MPa; the mechanical extruder uses a hole-type die with a specification of 3.0-5.0mm and an extrusion pressure of 0.2-0.7T; the extrusion ball making machine uses a hole-type die with a specification of 4.0mm, an extrusion rate of 2m / min, and a cutting rate of 500 particles / min.

[0025] (8) drying the precursor G in the shade at 30-50° C. for 10-20 h, then heating to 120-150° C. for drying for 6-12 h, and then calcining in air at 400-550° C. for 4-6 h to obtain the precursor H;

[0026] (9) The precursor H is sulfurized in a sulfur-containing atmosphere to obtain a finished catalyst after the sulfurization is completed.

[0027] As a preferred embodiment of the present application, the Zr, Ce, and La salts in step (1) correspond to zirconium carbonate, cerium nitrate, and lanthanum nitrate, respectively. When the selected salt contains Zr, a nitric acid solution with a mass concentration of 5% is added to assist in dissolution according to the dissolution conditions.

[0028] As a better implementation in the present application, the soluble salt of the active component one in step (3) is any one of iron nitrate, copper nitrate, zinc nitrate, and cobalt nitrate, or a mixture of several of them.

[0029] As a preferred embodiment of the present application, the soluble salt of the active component 2 in step (6) is any one or a mixture of several of nickel nitrate, ammonium heptamolybdate, sodium molybdate, potassium molybdate, chromium nitrate, and ammonium metatungstate;

[0030] As a better embodiment of the present application, the active auxiliary agent in step (7) is any one of boric acid and boron nitride or a mixture of two of them, more preferably boric acid or boron nitride; the release agent is any one of graphite, magnesium stearate, and calcium stearate or a mixture of several of them; the acid is any one of citric acid, oxalic acid, ethylenediaminetetraacetic acid, and nitrilotriacetic acid or a mixture of several of them.

[0031] As a preferred embodiment of the present application, the sulfur-containing atmosphere in step (9) is a mixture of any one or more of carbon disulfide, dimethyl disulfide, ethyl mercaptan, and diethyl sulfide, and then mixed with nitrogen and hydrogen; more preferably, the total sulfur content of any one or more of the mixture of carbon disulfide, dimethyl disulfide, ethyl mercaptan, and diethyl sulfide is 0.5-5g / Nm 3 , the hydrogen content is 60-80%, and the rest is nitrogen; the sulfurization conditions are: temperature 380-400℃, air velocity 500-2000h -1 , pressure 0.2-2MPa, time 8-12h.

[0032] The present invention protects a catalyst for hydrogenation conversion of organic sulfur in raw gas prepared by any of the above methods or a combination of method steps.

[0033] Preferably, the shape of the finished catalyst is spherical, cylindrical or clover-shaped; the radial dimension of the catalyst is 3-5 mm, the axial dimension is 5-40 mm, and the radial strength is ≥60 N / cm.

[0034] The present invention also protects the use of a catalyst for hydrogenation conversion of organic sulfur in raw gas prepared by any of the above methods or a combination of method steps in hydrogenation conversion and deoxygenation of raw gas containing trace amounts of organic sulfur in coal chemical industry, petrochemical industry and other raw gases.

[0035] As a preferred embodiment of the present application, the above-mentioned catalyst for hydrogenation conversion of organic sulfur in raw gas has the following conditions for use of the finished product: temperature 220-300°C, raw gas space velocity 1000-8000h -1 , the total organic sulfur content in the raw gas is ≤100ppm, the oxygen content is ≤1.5%, and the pressure is 0.2-2MPa.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) In the present invention, the pore-forming agent introduced in combination with other materials can improve the specific surface area and pore size of the finished catalyst. The rich pore structure can increase the active sites and improve the conversion rate of organic sulfur, especially sulfur-containing macromolecules (such as thiophene, tetrahydrothiophene, etc.). Compared with traditional organic sulfur hydrogenation catalysts, the thiophene conversion rate of the catalyst prepared by the present invention is increased by more than 30%, the carbonyl sulfide conversion rate is increased by more than 20%, and the ethyl sulfide conversion rate is increased by more than 15%.

[0038] (2) In the present invention, oxygen in the feed gas can dissociate on the catalyst surface, and the generated active oxygen further reacts with other activated components in the atmosphere, avoiding the adverse effects of excessive oxygen content on subsequent process stages; in addition, there is a certain synergistic effect between the metal components in the catalyst, such as Ce, Fe, and Co, which improves the oxygen removal efficiency. Compared with existing desulfurization and deoxygenation catalysts, the catalyst prepared by the present invention can reduce the outlet oxygen concentration from >1000ppm to <80ppm, basically eliminating the production safety hazards caused by excessive oxygen concentration or drastic fluctuations in a short period of time.

[0039] (3) In the present invention, pseudo-boehmite with rich surface groups is selected as a carrier, and metals such as Ce, Zr, and La are firmly loaded on the carrier through a co-precipitation method, thereby strengthening the anchoring effect between the carrier and the modified metal component, and to a certain extent avoiding the adverse effects such as loss of active components, sintering of active metals, and destruction of pore structure caused by long-term use.

[0040] (4) In the present invention, the added active additive can form an XOY chemical bond (X is the carrier metal element, Y is the element contained in the active additive) on the surface of the composite oxide carrier, thereby inhibiting the active components from entering the carrier lattice, effectively improving the dispersion of the active components, enhancing the catalytic hydrogenation activity, and slowing down the deactivation rate of the catalyst.

[0041] (5) In the present invention, certain specific acids are introduced during the molding process, which can effectively complex with free metal ions, prevent the aggregation of active metal components, increase the dispersion of active components and thus form more active sites. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the structure of an evaluation device for a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas in the present invention;

[0043] Figure numerals: 1 is a pressure reducing valve for a sulfur-containing gas cylinder, 4 is a pressure reducing valve for a nitrogen cylinder, 2 and 5 are flow meters, 3, 6, 9, 10, 15, 17 and 21 are ball valves, 7 is a gas buffer tank, 8 is a preheater, 11, 16 and 18 are needle valves, 12 is a fixed bed reactor, 13 is a tubular heating furnace, 14 is a back pressure valve, 19 is a sulfur analyzer, 20 is an oxygen analyzer, and 22 and 23 are sulfide absorption tanks. DETAILED DESCRIPTION

[0044] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0045] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other alternative features that are equivalent or have similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0046] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0047] All the following raw materials are commercially available products; % not otherwise specified indicates the mass percentage, i.e. wt%.

[0048] Pseudoboehmite is prepared by alcohol aluminum method, and the impurity content is less than 0.1%.

[0049] Embodiment 1:

[0050] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 73%, an active component one accounts for 9%, an active component two accounts for 12%, an active auxiliary agent accounts for 2%, a release agent accounts for 2.5%, a pore-forming agent accounts for 1.5%, and the sum of the total mass percentages is 100%.

[0051] The specific preparation steps of the catalyst are:

[0052] (1) Weigh 5.84 g of lanthanum nitrate hexahydrate and 7.07 g of cerium nitrate hexahydrate, add 120 g of deionized water, place in a 40°C water bath and stir to dissolve, then weigh 140.0 g of pseudo-boehmite powder and add to the above solution, and stir at 400 rpm for 3 h to obtain a solid-liquid mixed slurry A1.

[0053] (2) Weigh 50 g of sodium carbonate and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A1 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 6 h. Then, filter and wash three times, then dry at 120°C for 8 h, and then calcine at 600°C in air for 5 h to obtain precursor B1.

[0054] (3) Weigh 65.65 g of ferric nitrate nonahydrate and dissolve it in 109.45 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve the mixture to obtain a precursor solution C1.

[0055] (4) Precursor B1 and precursor solution C1 were added into a closed mud mixer and mechanically mixed for 2 h at an absolute pressure of 0.005 MPa to obtain precursor D1.

[0056] (5) Precursor D1 was dried in the shade at 40°C for 15 h, then heated to 120°C and dried for 8 h, and then calcined in air at 500°C for 4 h to obtain precursor E1.

[0057] (6) Weigh 48.96 g of chromium nitrate nonahydrate and 30.99 g of nickel nitrate hexahydrate, dissolve them in 101.5 g of deionized water, place them in a 40° C. water bath, and stir to dissolve, to obtain a precursor solution F1.

[0058] (7) Weigh 16.42 g of boric acid, 3.59 g of calcium stearate, 2.16 g of polyacrylamide, and 48.03 g of citric acid monohydrate, add the precursor E1 and the precursor solution F1 into a closed mud kneader, mechanically mix for 3 h at an absolute pressure of 0.005 MPa, and then extrude into strips using a mechanical extruder to obtain precursor G1. The mechanical extruder uses a 3.0 mm hole die and an extrusion pressure of 0.68 T.

[0059] (8) The precursor F1 was dried in the shade at 40° C. for 15 h, then heated to 120° C. for drying for 10 h, and then calcined in air at 500° C. for 5 h to obtain the precursor H1;

[0060] (9) Precursor G1 was placed in a tube furnace at 380°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I1.

[0061] Embodiment 2:

[0062] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 70%, an active component one accounts for 8%, an active component two accounts for 13.5%, an active auxiliary agent accounts for 3%, a release agent accounts for 3%, a pore-forming agent accounts for 2.5%, and the sum of the total mass percentages is 100%.

[0063] The specific preparation steps of the catalyst are:

[0064] (1) Weigh 1.25 g of lanthanum nitrate hexahydrate and 4.84 g of cerium nitrate hexahydrate, add 115 g of deionized water, place in a 40°C water bath and stir to dissolve, then weigh 140 g of pseudo-boehmite powder and add to the above solution, and stir at 400 rpm for 2.5 h to obtain a solid-liquid mixed slurry A2.

[0065] (2) Weigh 50 g of potassium carbonate and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A2 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 6 h. Then, filter and wash three times, then dry at 120°C for 8 h, and then calcine at 600°C in air for 6 h to obtain precursor B2.

[0066] (3) Weigh 35.28 g of copper nitrate trihydrate and dissolve it in 122.87 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve the mixture to obtain a precursor solution C2.

[0067] (4) Precursor B2 and precursor solution C2 were added into a closed mud mixer and mechanically mixed for 4 h at an absolute pressure of 0.01 MPa to obtain precursor D2.

[0068] (5) Precursor D2 was dried in the shade at 50°C for 12 h, then heated to 120°C and dried for 10 h, and then calcined in air at 480°C for 5 h to obtain precursor E2.

[0069] (6) Weigh 55.11 g of chromium nitrate nonahydrate and 35.81 g of nickel nitrate hexahydrate, dissolve them in 118.23 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution F2.

[0070] (7) Weigh 25.02 g of boric acid, 2.19 g of calcium stearate, 2.16 g of magnesium stearate, 3.66 g of polymethyl methacrylate, and 32.91 g of oxalic acid dihydrate, add them together with the precursor E2 and the precursor solution F2 into a closed mud kneader, mechanically mix them at an absolute pressure of 0.01 MPa for 4 h, and then extrude them into strips using a mechanical extruder to obtain the precursor G2. The mechanical extruder uses a 4.0 mm hole die and an extrusion pressure of 0.56 T.

[0071] (8) Precursor G2 was dried in the shade at 40°C for 12 h, then heated to 120°C for drying for 10 h, and then calcined in air at 480°C for 5 h to obtain precursor H2;

[0072] (9) The precursor H2 was placed in a tube furnace at 400°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Dimethyl disulfide, space velocity 1000h -1 The mixture was sulfurized for 12 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I2.

[0073] Embodiment 3:

[0074] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 78%, an active component one accounts for 7.5%, an active component two accounts for 9.3%, an active auxiliary agent accounts for 1.6%, a release agent accounts for 1.8%, a pore-forming agent accounts for 1.8%, and the sum of the total mass percentages is 100%.

[0075] The specific preparation steps of the catalyst are:

[0076] (1) Weigh 5.29 g of lanthanum nitrate hexahydrate, 3.48 g of zirconium carbonate, and 6.56 g of cerium nitrate hexahydrate, add 100 g of deionized water, and then add 25 g of nitric acid solution. After mixing, place in a 40°C water bath and stir to dissolve. Then weigh 140 g of pseudo-boehmite powder and add it to the above solution. Stir at 400 rpm for 4 h to obtain a solid-liquid mixed slurry A3.

[0077] (2) Weigh 20 g of ammonia water and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A3 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 7 h. Then, filter and wash three times, then dry at 120°C for 10 h, and then calcine at 600°C in air for 6 h to obtain precursor B3.

[0078] (3) Weigh 31.76 g of ferric nitrate nonahydrate and 14.66 g of zinc nitrate hexahydrate, dissolve them in 111.53 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution C3.

[0079] (4) Precursor B3 and precursor solution C3 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.005 MPa for 3 h to obtain precursor D3.

[0080] (5) Precursor D3 was dried in the shade at 45°C for 15 h, then heated to 135°C and dried for 8.5 h, and then calcined in air at 450°C for 5 h to obtain precursor E3.

[0081] (6) Weigh 6.77 g of sodium molybdate dihydrate and 9.39 g of ammonium metatungstate and dissolve them in 122.46 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve, thereby obtaining a precursor solution F3.

[0082] (7) 9.15 g of boric acid, 1.86 g of boron nitride, 1.11 g of calcium stearate, 1.37 g of graphite, 2.48 g of polymethyl methacrylate, and 13.78 g of citric acid monohydrate were weighed and added into a closed mud mill together with the precursor D3 and the precursor solution F3. The mixture was mechanically mixed at an absolute pressure of 0.005 MPa for 4 h, and then pressed into balls using an extrusion ball making machine.

[0083] (8) Precursor G3 was dried in the shade at 50°C for 10 h, then heated to 120°C and dried for 9 h, and then calcined in air at 530°C for 5 h to obtain precursor H3.

[0084] (9) The precursor H3 was placed in a tube furnace at 400°C, 0.8 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1The mixture was sulfurized for 12 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I3.

[0085] Embodiment 4:

[0086] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 82%, an active component one accounts for 5.0%, an active component two accounts for 8.7%, an active auxiliary agent accounts for 1.3%, a release agent accounts for 1.5%, a pore-forming agent accounts for 1.5%, and the sum of the total mass percentages is 100%.

[0087] The specific preparation steps of the catalyst are:

[0088] (1) Weigh 10.39 g of lanthanum nitrate hexahydrate and 5.55 g of cerium nitrate hexahydrate, add 120 g of deionized water, mix, and place in a 40°C water bath to stir and dissolve. Then weigh 140 g of pseudo-boehmite powder and add it to the above solution, and stir at 400 rpm for 2 h to obtain a solid-liquid mixed slurry A4.

[0089] (2) Weigh 50 g of sodium carbonate and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A4 until the pH value of the solution reaches 9.9, and then stir at 400 rpm for 7 h. Then, filter and wash three times, then dry at 120°C for 8 h, and then calcine at 600°C in air for 5 h to obtain precursor B4.

[0090] (3) Weigh 32.62 g of ferric nitrate nonahydrate and dissolve it in 118.57 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve, thereby obtaining a precursor solution C4.

[0091] (4) Precursor B4 and precursor solution C4 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.009 MPa for 2 h to obtain precursor D4.

[0092] (5) Precursor D4 was dried in the shade at 35°C for 18 h, then heated to 120°C and dried for 8 h, and then calcined in air at 450°C for 5 h to obtain precursor E4.

[0093] (6) Weigh 9.96 g of nickel nitrate hexahydrate and 9.66 g of ammonium metatungstate and dissolve them in 138.89 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve, thereby obtaining a precursor solution F4.

[0094] (7) Weigh 4.18 g of boric acid, 2.19 g of boron nitride, 1.96 g of graphite, 1.96 g of polyacrylamide, and 14.82 g of nitrilotriacetic acid, add them together with the precursor E4 and the precursor solution F4 into a closed mud kneader, mechanically mix them for 4 h at an absolute pressure of 0.009 MPa, and then extrude them into strips using a mechanical extruder to obtain the precursor G4. The mechanical extruder uses a 5.0 mm hole die and an extrusion pressure of 0.49 T.

[0095] (8) Precursor G4 was dried in the shade at 35°C for 12 h, then heated to 120°C for drying for 8 h, and then calcined at 450°C in air for 5.5 h to obtain precursor H4;

[0096] (9) The precursor H4 was placed in a tube furnace at 380°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I4.

[0097] Embodiment 5:

[0098] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 85%, an active component one accounts for 5.4%, an active component two accounts for 6.0%, an active auxiliary agent accounts for 1.1%, a release agent accounts for 1.2%, a pore-forming agent accounts for 1.3%, and the sum of the total mass percentages is 100%.

[0099] The specific preparation steps of the catalyst are:

[0100] (1) Weigh 1.66 g of zirconium carbonate and 9.61 g of cerium nitrate hexahydrate, add 105 g of deionized water, then add 15 g of nitric acid solution, mix, place in a 40°C water bath, stir and dissolve, then weigh 140 g of pseudo-boehmite powder, add to the above solution, and stir at 400 rpm for 4 h to obtain a solid-liquid mixed slurry A5.

[0101] (2) Weigh 20 g of ammonia water and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A5 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 6 h. Then, filter and wash three times, then dry at 120°C for 10 h, and then calcine at 650°C in air for 6 h to obtain precursor B5.

[0102] (3) Weigh 10.22 g of copper nitrate trihydrate and 12.10 g of zinc nitrate hexahydrate, dissolve them in 124.22 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution C5.

[0103] (4) Precursor B5 and precursor solution C5 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.01 MPa for 3 h to obtain precursor D5.

[0104] (5) Precursor D5 was dried in the shade at 35°C for 18 h, then heated to 130°C for drying for 6 h, and then calcined in air at 510°C for 5 h to obtain precursor E5.

[0105] (6) Weigh 12.22 g of potassium molybdate and dissolve it in 138.28 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve, thereby obtaining a precursor solution F5.

[0106] (7) 7.78 g of boric acid, 0.55 g of calcium stearate, 0.93 g of graphite, 0.60 g of polyacrylamide, and 15.04 g of ethylenediaminetetraacetic acid were weighed and added into a closed mud mill together with the precursor E5 and the precursor solution F5. The mixture was mechanically mixed at an absolute pressure of 0.01 MPa for 3 h, and then pressed into balls using an extrusion ball making machine.

[0107] (8) Precursor G5 was dried in the shade at 30°C for 15 h, then heated to 130°C and dried for 6 h, and then calcined in air at 510°C for 4.5 h to obtain precursor H5.

[0108] (9) Precursor H5 was placed in a tube furnace at 380°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Dimethyl disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I5.

[0109] Embodiment 6:

[0110] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 66%, an active component one accounts for 10.2%, an active component two accounts for 12.8%, an active auxiliary agent accounts for 3.2%, a release agent accounts for 3.6%, a pore-forming agent accounts for 4.2%, and the sum of the total mass percentages is 100%.

[0111] The preparation method of the catalyst is:

[0112] (1) Weigh 5.31 g of lanthanum nitrate hexahydrate and 8.10 g of cerium nitrate hexahydrate, add 120 g of deionized water, mix, and place in a 40°C water bath to stir and dissolve. Then weigh 140 g of pseudo-boehmite powder and add it to the above solution, and stir at 400 rpm for 3 h to obtain a solid-liquid mixed slurry A6.

[0113] (2) Weigh 20 g of ammonia water and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A6 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 7 h. Then, filter and wash three times, then dry at 120°C for 8 h, and then calcine at 650°C in air for 5 h to obtain precursor B6.

[0114] (3) Weigh 45.61 g of ferric nitrate nonahydrate and 21.83 g of copper nitrate trihydrate, dissolve them in 114.23 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution C6.

[0115] (4) Precursor B6 and precursor solution C6 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.003 MPa for 2 h to obtain precursor D6.

[0116] (5) Precursor D6 was dried in the shade at 42°C for 13 h, then heated to 125°C and dried for 9 h, and then calcined in air at 460°C for 5.5 h to obtain precursor E6.

[0117] (6) Weigh 17.60 g of chromium nitrate nonahydrate and 79.44 g of nickel nitrate hexahydrate, dissolve them in 109.89 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution F6.

[0118] (7) Weigh 29.20 g of boric acid, 2.01 g of boron nitride, 1.90 g of calcium stearate, 1.93 g of magnesium stearate, 1.92 g of graphite, 2.31 g of polyacrylamide, 4.38 g of linear phenolic resin, 21.01 g of oxalic acid dihydrate, and 28.78 g of nitrilotriacetic acid, and add them together with the precursor E6 and the precursor solution F6 into a closed mud kneader, mechanically mix them at an absolute pressure of 0.003 MPa for 4 h, and then extrude them into strips using a mechanical extruder to obtain the precursor G6. The mechanical extruder uses a 4.0 mm hole die and an extrusion pressure of 0.58 T.

[0119] (8) Precursor G6 was dried in the shade at 35°C for 15 h, then heated to 120°C and dried for 9 h, and then calcined in air at 480°C for 6 h to obtain precursor H6.

[0120] (9) Precursor H6 was placed in a tube furnace at 380°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I6.

[0121] Embodiment 7:

[0122] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 80%, an active component one accounts for 6.1%, an active component two accounts for 7.8%, an active auxiliary agent accounts for 2.2%, a release agent accounts for 2.2%, a pore-forming agent accounts for 2.3%, and the sum of the total mass percentages is 100%.

[0123] The preparation method of the catalyst is:

[0124] (1) Weigh 12.20 g of cerium nitrate hexahydrate, add 120 g of deionized water, mix, and place in a 40°C water bath to stir and dissolve. Then weigh 140 g of pseudo-boehmite powder and add it to the above solution. Stir at 400 rpm for 3 h to obtain a solid-liquid mixed slurry A7.

[0125] (2) Weigh 50 g of sodium carbonate and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A7 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 6 h. Then, filter and wash three times, then dry at 120°C for 10 h, and then calcine at 700°C in air for 6 h to obtain precursor B7.

[0126] (3) Weigh 5.33 g of cobalt nitrate hexahydrate and 20.27 g of copper nitrate trihydrate, dissolve them in 125.68 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution C7.

[0127] (4) Precursor B7 and precursor solution C7 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.001 MPa for 2 h to obtain precursor D7.

[0128] (5) Precursor D7 was dried in the shade at 50°C for 10 h, then heated to 150°C and dried for 8 h, and then calcined in air at 550°C for 6 h to obtain precursor E7.

[0129] (6) Weigh 12.22 g of potassium molybdate and 3.09 g of ammonium metatungstate and dissolve them in 139.38 g of deionized water. Place the mixture in a 40° C. water bath and stir to dissolve, thereby obtaining a precursor solution F7.

[0130] (7) 16.48 g of boric acid, 2.88 g of graphite, 1.68 g of polymethyl methacrylate, 1.33 g of linear phenolic resin, and 13.38 g of citric acid monohydrate were weighed and added to a closed mud mill together with the precursor E7 and the precursor solution F7. The mixture was mechanically mixed for 2 h at an absolute pressure of 0.001 MPa, and then extruded into strips using a mechanical extruder to obtain the precursor G7. The mechanical extruder selected a 5.0 mm hole die and an extrusion pressure of 0.48 T.

[0131] (8) Precursor G7 was dried in the shade at 50°C for 18 h, then heated to 140°C and dried for 8 h, and then calcined in air at 510°C for 6 h to obtain precursor H7.

[0132] (9) Precursor H7 was placed in a tube furnace at 390°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I7.

[0133] Embodiment 8:

[0134] A dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in raw gas, in which a carrier accounts for 76%, an active component one accounts for 5.2%, an active component two accounts for 11.8%, an active auxiliary agent accounts for 2.8%, a release agent accounts for 2.2%, a pore-forming agent accounts for 2.0%, and the sum of the total mass percentages is 100%.

[0135] The preparation method of the catalyst is:

[0136] (1) Weigh 2.82 g of cerium nitrate hexahydrate and 10.0 g of lanthanum nitrate hexahydrate, add 120 g of deionized water, mix, and place in a 40°C water bath to stir and dissolve. Then weigh 140 g of pseudo-boehmite powder and add it to the above solution, and stir at 400 rpm for 2 h to obtain a solid-liquid mixed slurry A8.

[0137] (2) Weigh 20 g of ammonia water and add it to 2000 mL of deionized water. After stirring to dissolve, use a pump to pump it into the solid-liquid mixed slurry A8 until the pH value of the solution reaches 10.0, and then stir at 400 rpm for 7 h. Then, filter and wash three times, then dry at 120°C for 10 h, and then calcine at 650°C in air for 6 h to obtain precursor B8.

[0138] (3) Weigh 7.99 g of zinc nitrate hexahydrate and 25.26 g of ferric nitrate nonahydrate, dissolve them in 122.01 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution C8.

[0139] (4) Precursor B8 and precursor solution C8 were mechanically mixed together in a closed mud mill at an absolute pressure of 0.02 MPa for 3 h to obtain precursor D8.

[0140] (5) Precursor D8 was dried in the shade at 50°C for 12 h, then heated to 120°C and dried for 10 h, and then calcined in air at 500°C for 6 h to obtain precursor E8.

[0141] (6) Weigh 66.86 g of chromium nitrate nonahydrate and 13.98 g of nickel nitrate hexahydrate, dissolve them in 115.88 g of deionized water, place them in a 40° C. water bath, and stir to dissolve them to obtain a precursor solution F8.

[0142] (7) Weigh 22.05 g of boric acid, 2.05 g of graphite, 1.00 g of calcium stearate, 2.76 g of linear phenolic resin, and 27.18 g of oxalic acid dihydrate, add them together with the precursor E8 and the precursor solution F8 into a closed mud mill, mechanically mix them at an absolute pressure of 0.02 MPa for 3 h, and then use an extrusion ball making machine to press them into balls.

[0143] (8) Precursor G8 was dried in the shade at 50°C for 12 h, then heated to 120°C and dried for 10 h, and then calcined in air at 500°C for 6 h to obtain precursor H8.

[0144] (9) Precursor H8 was placed in a tube furnace at 390°C, 0.5 MPa, 25% nitrogen, 50% hydrogen, 5 g / Nm 3 Carbon disulfide, space velocity 1000h -1 The mixture was sulfurized for 10 h under the above conditions and then cooled to room temperature to obtain the finished catalyst I8.

[0145] Comparative Example 1:

[0146] This comparative example was prepared according to the method disclosed in Example 1 of Chinese Patent CN 108855116 A, specifically:

[0147] (1) Dissolve 18 g of ammonium molybdate, 3 g of nickel nitrate, 30 g of ferric nitrate and 10 g of acetic acid in 150 g of deionized water and stir to mix well;

[0148] (2) adding the above solution to 300 g of pseudo-boehmite and 15 g of sesbania powder, kneading, extruding, drying at 100° C. for 4 h, and calcining at 480° C. for 6 h;

[0149] (3) The catalyst prepared above is sulfurized to obtain the finished catalyst I9.

[0150] Comparative Example 2:

[0151] This comparative example was prepared according to the method disclosed in Example 2 of Chinese Patent CN 113171778 A, specifically:

[0152] (1) Glycerol, ethanol and ether were mixed in a volume ratio of 1:2:1 to obtain a mixed solution, and then 2.0 g of TiOSO4·2H2O was added to 10 mL of the mixed solution, and ultrasonic stirring was performed at room temperature for 15 h to obtain a white suspension A, and then the white suspension A was transferred to a high-pressure reactor and reacted at 180° C. for 16 h. After the reaction was completed, the reactant was cooled to room temperature, filtered to obtain a precipitate, and the precipitate was washed with anhydrous ethanol until neutral, and then the washed neutral precipitate was placed in an oven and dried at 30° C. for 3 h to obtain a titanium dioxide nanotube intermediate.

[0153] (2) adding a certain amount of 10 mol / L NaOH solution to the titanium dioxide nanotube intermediate obtained in step (1), mixing evenly to obtain a white suspension B, then transferring the white suspension B to a 100 mL high-pressure reactor, adding an appropriate amount of a mixed solution of a cobalt nitrate solution and a molybdenum nitrate solution with a Co:Mo molar ratio of 1:5-1:7, and reacting at a temperature of 150° C. for 24 hours;

[0154] (3) After the reaction is completed, the mixture is pickled with 0.1 mol / L hydrochloric acid for 24 h, filtered, and the solid residue is washed with deionized water until it is neutral and placed in an oven for drying at 80° C. for 14 h, then rapidly heated to 120° C. and continued to be dried for 4 h. Finally, the obtained material is calcined at 400° C. for 4 h to obtain a coke oven gas deep purification desulfurizer in which Co and Mo active components are uniformly dispersed on the surface of titanium dioxide nanotubes;

[0155] (4) The catalyst was sulfided for 6 h in a mixed gas atmosphere of H2:CS2=97:3 and at a temperature of 380°C to obtain a finished catalyst I10.

[0156] Comparative Example 3:

[0157] This comparative example was prepared according to the method disclosed in Example 4 of Chinese Patent CN 105435806 A, specifically in the following manner:

[0158] (1) 36.1gC 16 H 36 O4Ti was dissolved in 100g water, and then 76.5g alumina balls were immersed in the prepared titanium salt solution, immersed at room temperature for 8 hours, dried at 100℃ for 4 hours, and calcined at 600℃ for 3 hours to obtain TiO2-Al2O3 carrier;

[0159] (2) 3 g MoO3, 3.9 g Ni(NO3)2.6H2O, 3.3 g Co(CH3COO)2·4H2O and 10.4 g hydrofluoric acid were dissolved in 100 g water to prepare a mixed impregnation solution;

[0160] (3) The carrier prepared in step (1) was immersed in the mixed impregnation solution of step (2) for 8 hours at room temperature, dried at 120°C for 2 hours, and calcined at 500°C for 3 hours to obtain the finished catalyst I11.

[0161] Comparative Example 4:

[0162] The preparation of the catalyst in this comparative example is the same as that in Example 1, the only difference is that 16.42 g of boric acid in step (7) of Example 1 is changed to 9.07 g of phosphoric acid (the mass of the phosphorus atom after the change is the same as the mass of the boron atom before the change), and the remaining steps are consistent with Example 1 to obtain the finished catalyst I12.

[0163] Comparative Example 5:

[0164] The preparation method of the catalyst in this comparative example is the same as that in Example 1, the only difference is that 48.03 g of citric acid monohydrate in step (7) of Example 1 is changed to 13.72 g of glacial acetic acid (the amount of glacial acetic acid after the change is the same as the amount of citric acid monohydrate before the change), and the remaining steps are consistent with Example 1 to obtain the finished catalyst I13.

[0165] Comparative Example 6:

[0166] The preparation method of the catalyst in this comparative example is the same as that in Example 1, the only difference is that 5.84 g of lanthanum nitrate hexahydrate and 7.07 g of cerium nitrate hexahydrate in step (1) of Example 1 are replaced with 11.10 g of holmium nitrate pentahydrate (the mass of the holmium atom after the change is the same as the sum of the atomic masses of lanthanum and cerium before the change), and the remaining steps are consistent with Example 1 to obtain the finished catalyst I14.

[0167] Evaluation method

[0168] 1. Raw gas composition

[0169] (1) Thiophene 100 ppm, oxygen 1.5%, other components: carbon monoxide 10%, carbon dioxide 3%, methane 20%, ethane 5%, ethylene 2%, nitrogen 2%, and the rest is hydrogen.

[0170] (2) Carbonyl sulfide 100 ppm, oxygen 1.5%, other components: carbon monoxide 10%, carbon dioxide 3%, methane 20%, ethane 5%, ethylene 2%, nitrogen 2%, and the rest is hydrogen.

[0171] (3) Ethyl sulfide 100 ppm, oxygen 1.5%, other components: carbon monoxide 10%, carbon dioxide 3%, methane 20%, ethane 5%, ethylene 2%, nitrogen 2%, and the rest is hydrogen.

[0172] 2. Test device, see Figure 1 Schematic diagram of the evaluation device structure of the dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in the feed gas, with the specific steps as follows:

[0173] The sulfur-containing raw gas enters the pipeline through the sulfur-containing gas cylinder pressure reducing valve 1, flow meter 2 and ball valve 3, and is mixed with the nitrogen from the nitrogen cylinder pressure reducing valve 4, flow meter 5 and ball valve 6, and then enters the gas buffer tank 7 for buffering. The buffered mixed gas is preheated by the preheater 8 and then divided into two parts. One part enters the fixed bed reactor 12 through the ball valve 9. The fixed bed reactor 12 is filled with inert porcelain balls, desulfurizer, and inert porcelain balls from bottom to top in sequence; the fixed bed reactor 12 is equipped with a heating device Tubular heating furnace 13; the reacted substances are divided after passing through the back pressure valve 14, and a part of them passes through the ball valve 15 and the needle valve 16 together with the other part of the substances coming through the ball valve 10 and the needle valve 11, and then enter the sulfide absorption tank 22 and the sulfide absorption tank 23 in sequence after passing through the ball valve 21; another part of the substances coming out of the back pressure valve 14 enters the sulfide absorption tank together with the substances after passing through the oxygen analyzer 20 through the ball valve 17 and the needle valve 18.

[0174] 3. Test conditions

[0175] Temperature 300℃, raw gas space velocity 8000h -1 , pressure 1.0MPa.

[0176] 4. Test results

[0177] The test results of organic sulfur catalytic conversion rate and outlet oxygen concentration are shown in Table 1.

[0178] Table 1 Test results of organic sulfur conversion rate and outlet oxygen concentration

[0179]

[0180] The best embodiment of the present invention is embodiment 6, which has a high conversion rate for thiophene, carbonyl sulfide and diethyl sulfide, and a low outlet oxygen concentration. Compared with other embodiments, the bifunctional catalyst prepared in embodiment 6 has the least decrease in the conversion rate of the above sulfur-containing organic matter after running for 500 hours, and the strength is greater than 70N / cm, which can ensure the stability during continuous operation in industrial devices. The degree of decrease in the organic sulfur conversion rate after the catalysts in embodiments 3, 4 and 7 run for 500 hours is slightly higher. By comparing with embodiment 6, the results show that by increasing the proportion of pore-forming agent added, the catalyst pore volume and pore size can be increased, which helps to counteract the decrease in organic sulfur conversion rate caused by carbon deposition.

[0181] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

[0182] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.

Claims

1. A bifunctional catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas, characterized in that: In terms of mass percentage, the catalyst includes 65-85% of a carrier, 5-15% of an active component one, 5-15% of an active component two, 1-5% of an active auxiliary agent, 1-5% of a release agent and 1-5% of a pore-forming agent, and the total mass percentage is 100%; the carrier is a composite oxide material; the active component one is any one of Fe2O3, CuO, ZnO, CoO or a mixture of several thereof; the active component two is any one of NiO, MoO3, Cr2O3, WO3 or a mixture of several thereof.

2. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 1, characterized in that: The steps include: (1) Weigh any one or a combination of Zr, Ce, and La salts, add them to an appropriate amount of deionized water, place them in a 40-60° C. water bath, and stir to dissolve, then weigh pseudo-boehmite powder and add it to the above solution, and stir to obtain a solid-liquid mixed slurry A; (2) Weigh a certain amount of sodium carbonate, potassium carbonate or ammonia water or a combination thereof, add it to an appropriate amount of deionized water, stir and dissolve it, and then use a pump to pump it into the solid-liquid mixed slurry A until the pH value of the solution is 9.8-10.0, then stir at 400 rpm for 4-12 hours, filter and wash three times after stirring, then dry at 120° C. for 6-12 hours, and then calcine at 600-800° C. in air for 5-10 hours to obtain a precursor B; (3) Weigh a certain amount of soluble salt of active component 1, add an appropriate amount of deionized water, place in a 40-60° C. water bath, stir and dissolve to obtain a precursor solution C; (4) mechanically mixing the precursor B and the precursor solution C in a closed mud mixer for 2-4 hours to obtain a precursor D; The absolute pressure in the closed mud mixer is 0.001-0.05MPa; (5) drying the precursor D in the shade at 30-50° C. for 10-20 h, then heating to 120-150° C. for drying for 6-12 h, and then calcining in air at 400-550° C. for 4-6 h to obtain a precursor E; (6) Weigh a certain amount of soluble salt of active component 2, add an appropriate amount of deionized water, place in a 40-60° C. water bath, stir and dissolve to obtain a precursor solution F; (7) Weigh a certain amount of active additive, release agent and pore-forming agent, place them together with the precursor E in a closed mud kneading machine, then add the precursor solution F and the acid with the same mass as the precursor solution F, mix and knead for 2-4 hours; then use a mechanical extruder or an extrusion ball machine to extrude and mold to obtain a precursor G; the absolute pressure in the closed mud kneading machine is 0.001-0.05MPa; the mechanical extruder uses a hole-shaped die with a specification of 3.0-5.0mm, and the extrusion pressure is 0.2-0.7T; the extrusion ball machine uses a hole-shaped die with a specification of 4.0mm, an extrusion rate of 2m / min, and a cutting rate of 500 particles / min; (8) drying the precursor G in the shade at 30-50° C. for 10-20 h, then heating to 120-150° C. for drying for 6-12 h, and then calcining in air at 400-550° C. for 4-6 h to obtain the precursor H; (9) The precursor H is sulfurized in a sulfur-containing atmosphere to obtain a finished catalyst after the sulfurization is completed.

3. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 2, characterized in that: The Zr, Ce and La salts described in step (1) correspond to zirconium carbonate, cerium nitrate and lanthanum nitrate respectively; when the selected salt contains Zr, a nitric acid solution with a mass concentration of 5% is added for dissolution according to the dissolution situation.

4. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 2, characterized in that: The soluble salt of the active component 1 in step (3) is any one of ferric nitrate, copper nitrate, zinc nitrate and cobalt nitrate or a mixture of several of them.

5. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 2, characterized in that: The active component disoluble salt in step (6) is any one of nickel nitrate, ammonium heptamolybdate, sodium molybdate, potassium molybdate, chromium nitrate and ammonium metatungstate or a mixture of several thereof.

6. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 2, characterized in that: In step (7), the active auxiliary agent is one of boric acid and boron nitride or a mixture of two thereof; the release agent is one of graphite, magnesium stearate, and calcium stearate or a mixture thereof; the pore-forming agent is one of polyacrylamide, polymethyl methacrylate, and linear phenolic resin or a mixture thereof; and the acid is any one of citric acid, oxalic acid, ethylenediaminetetraacetic acid, and nitrilotriacetic acid or a mixture thereof.

7. The method for preparing a dual-function catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas according to claim 2, characterized in that: The sulfur-containing atmosphere in step (9) is a mixture of any one or more of carbon disulfide, dimethyl disulfide, ethyl mercaptan, and ethyl sulfide, and then a mixed atmosphere of nitrogen and hydrogen; wherein the total sulfur content of any one or more of the mixture of carbon disulfide, dimethyl disulfide, ethyl mercaptan, and ethyl sulfide is 0.5-5g / Nm 3 The vulcanization conditions are: temperature 380-400°C, air velocity 500-2000h -1 , pressure 0.2-2.0MPa, time 8-12h.

8. A bifunctional catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas prepared by the method according to any one of claims 2 to 7, characterized in that: The shape of the finished catalyst is spherical or cylindrical; the radial dimension of the catalyst is 3-5 mm, the axial dimension is 5-40 mm, and the radial strength is ≥60 N / cm.

9. Use of the bifunctional catalyst for hydrogenation conversion and deoxygenation of organic sulfur in feed gas as claimed in claim 8 in hydrogenation conversion and deoxygenation of trace organic sulfur in feed gas.

10. The use according to claim 9, characterized in that The catalyst is used under the following conditions: temperature 220-300°C, feed gas space velocity 1000-8000h -1 , the total organic sulfur content in the raw gas is ≤100ppm, the oxygen content is ≤1.5%, and the pressure is 0.2-2MPa.

Citation Information

Patent Citations

  • An organic sulfur hydrogenation catalyst and its preparation method

    CN103157481B

  • An organic sulfur hydrogenation catalyst and its preparation and use method

    CN103203236B

  • Deoxidation and organic sulfur hydro-conversion bifunctional catalyst, and preparation method and application thereof

    CN105435806A

  • Preparation method and application of efficient catalyst used for organic sulfur hydrogenation conversion

    CN107486223A

  • Low-loading-quantity coke oven gas hydrogen desulfurization catalyst as well as preparation method and application thereof

    CN108855116A